The Effect of Somatic Training on Improving Dancers’ Movement Quality: A Quasi-Experimental Study - Nur Winda Sari; Trianti Nugraheni; Fitri Kurniati (Universitas Negeri Semarang, 2026)
This study is motivated by the need to improve the movement quality of intermediate-level dancers. In practice, training tends to emphasize mastery of mechanical techniques and memorization of choreography, while body awareness and dancers’ sensory experiences have not been the primary focus. This condition indicates a gap between movement form mastery and conscious movement quality. Somatic practice, as a mind-body approach, offers an alternative training method that emphasizes movement learning through sensory awareness and internal body control. This study aims to analyze whether the implementation of somatic training can significantly improve the movement quality of intermediate-level dancers at Studio Purnamasari. This study employed a quantitative approach with a one-group pretest-posttest quasi-experimental design. Six intermediate-level dancers participated in the study. Data were collected through movement quality assessments before (pretest) and after (posttest) the implementation of somatic training. The results showed an increase in the average score from 75.82 (pretest) to 87.64 (posttest), with a significant difference (p < 0.05). These findings indicate that somatic training effectively improves dancers’ movement quality through enhanced body awareness, movement coordination, and control of energy and breathing. This study contributes empirically to the development of body-awareness-based training methods in non-formal dance education.